Clay-based Matrices Incorporating Radioactive Silts: A Case Study of Sediments from Spent Fuel Pool; AIP Conference Proceedings; Vol. 1938 : Isotopes: Technologies, Materials and Application (ITMA-2017) - Antonenko M. Mikhail; Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Grigoriev A. Alexander; Chubreev D. Dmitry (2018, 2018)
Title screen